Software Failure Impact on a Company’s Business Process Efficiency - Gruszczyński, Krzysztof; Małyszko, Jacek (Studia Oeconomica Posnaniensia, 2017)
Th e article discusses the subject of measuring the influence of softwarefailure rate on a company’s business process effi iency. We put forward the thesisthat it is possible to measure the impact of increasing failure rate on a user’s financial condition. The research is based on real data provided by KRUK S.A., which consists of two subsets: system failure logs and operational data. By searching for data outliers and by conducting a causal analysis, we tried to identify the days, which presented a high dependence of process effi ciency on the observed failure rate. As a result, we have shown that it is possible to discover a measurable outlier in the process effi ciency that is caused by a specifi c set of failures.